Human Capital Management Analysis and Organizational Cultures for New Entrance in Mining Contractors Services Company – PT ANP - Sendy Christin Sagita; Edi Hamdi (Journal Of Business, Finance, and Economics (JBFE), 2023)
Human Capital Management (HCM) is one of the factors that support the Company's sustainability. The Mining Contracting Service Company that PT ANP plans, require the superior human resources so that the business can run well, achieve the company's vision and mission, be able to win the competition and be sustainable. Various studies by organizational observers tend to acknowledge that organizational culture has a strong influence on the long-term performance and effectiveness of an organization. Empirical research has also produced a series about the importance of culture for improving organizational performance. Thus, culture is an important component in the ultimate success or failure of a business. Basically there are four types of corporate culture namely Hierarchy, Market, Clan and Adhocracy, for that in an effort to support the achievement of its vision and mission, PT ANP will encourage the application of corporate culture and values to every employee, including work clothes, company logos and office layout, so that employees will be able to produce optimal performance to achieve company success in accordance with company values, namely Ownership, Advances in Innovation, Motivation & Integrity, Ethics and Responsiveness.